CRITIQUING DELEGATED LEGISLATION ON PREVENTING SEXUAL HARASSMENT OF WOMEN IN INDIAN HIGHER EDUCATION INSTITUTIONS - Budhiartie, Arrie; Pradhan, David; Devi, Arti (Diponegoro Law Review, 2024)
Sexual harassment of women in the workplace is a serious issue in India, affecting all social and professional sectors, including elite higher education institutions. This problem violates women's fundamental rights to equality and livelihood, breaches professional ethics, and hampers the productivity and potential of many academics. Although the Indian Parliament enacted a comprehensive law in 2013 to address sexual harassment at workplaces, the implementation, especially in educational institutions, is flawed due to bureaucratic inefficiencies. There is a lack of unbiased analysis on how delegated regulations by administrative authorities undermine the law's intent. This research article conducts a legal analysis of the law's implementation in higher educational institutions, using doctrinal research methodology. It identifies subjective and ultra vires provisions introduced by ideologically driven bureaucrats that compromise the law's validity and effectiveness. The study highlights deviations in delegated legislation from the original law and suggests corrective measures to address significant flaws in the regulations framed by the University Grants Commission.